The Role of Brand Image and Product Innovation on Purchase Decisions Ades Bootled Water: The Mediating Effect of Customer Satisfaction (Study in Semarang City) - Muhammad Sufi Ali Imran (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the rapidly growing Indonesian bottled water industry driven by health awareness and urbanization, where brands like Ades face intense competition that demands strong Brand Image and product innovation. The objective is to analyze their influence on Semarang consumers' purchasing decisions with customer satisfaction as an intervening factor, using a quantitative survey method on an infinite population via incidental sampling (119 respondents), a 5-point Likert scale online questionnaire, and PLS-SEM analysis in SmartPLS 4. The results show that Brand Image (path coefficient 0.486, p<0.05) and product innovation (0.386, p<0.05) have a positive and significant effect on customer satisfaction and purchase decisions directly, while customer satisfaction has a weak direct effect (0.139, p=0.041); mediation is not significant (p>0.05), with the model explaining 78.7% of the variance. In conclusion, direct perceptions of Brand Image and innovation are the main drivers of purchasing everyday products like Ades, exceeding the mediating role of satisfaction.